Climate change and the aquaculture sector of Sarawak / Rosita Hamdan - Rosita , Hamdan (2017)
Aquaculture activities are an important contributor to the growth of the fisheries sector in Malaysia. However, climate changes provide major challenges in sustaining future outlook of the aquaculture sector. This study aims to investigate the impacts of climate change on Sarawak’s aquaculture sector by assessing the biophysical and socio-economic vulnerability of aquaculture production, and identifying potential adaptation strategies to cope with climate change risks. Three principal essays address the study’s three objectives. The first essay focused on the assessment of climate change impacts on the biophysical vulnerability of aquaculture production in Sarawak from a macro level perspective for pond and cage systems. Biophysical vulnerability factors (mean maximum temperature, mean minimum temperature, sunshine hours and the pond aquaculture farm size) were found to influence pond aquaculture production positively. The results showed that cage production is positively influenced by mean percentage relative humidity and negatively influenced by mean maximum temperature. The second essay focused on the farm level impact assessment of climate change impacts on the biophysical and socio-economic vulnerability of Sarawak’s aquaculture sector based on evaluation of the physical value (production) and the financial value (income). The water quality, change in precipitation, drought, and hydrological events are biophysical factors that have effects on socio-economic vulnerability, whilst financial and physical factors were important in determining aquaculture productivity. In terms of farmers’ income and livelihoods, the results further revealed that the aquaculture system and ethnicity (demographic factors), technology usage (physical asset), financial loans and off-farm income (financial assets), and farm size, dissolved oxygen depletion, and pandemic diseases (natural resources and environmental assets) were the significant factors influencing the socio-economic vulnerability of Sarawak’s aquaculture sector. The third essay identified the potential adaptation strategy to counter climate change risks in Sarawak, based on the comparison of three different farm management approaches with three different risk reduction strategies. The potential adaptation strategy for pond aquaculture in Sarawak is to implement a feed waste emission reduction with environmental restriction strategy; and for cage activities it was through a feed waste reduction implementation strategy. The study revealed that the marginal abatement costs of ponds are higher than for cage activities and if more stringent environmental regulation and restriction were to be imposed on farm production, the marginal abatement costs would increase. The results also suggested that effective resource allocation management in land used or space for aquaculture, fish feed management and working hours’ (labor) in farm help would assist profit maximization for farms as well as reduce the climate change risks to aquaculture production. This study contributes towards an economic approach in the assessment of vulnerability to climate change risks and the potential adaptation option for Sarawak’s aquaculture sector. The assessment provided empirical evidence that the existing climate change risks and hazards in the aquaculture sector might worsen and imperil the aquaculture sector’s potential for future growth. The results of this study and recommendations made are important to improve current aquaculture management, policies, laws, and regulations in Malaysia to cope with climate change impacts.